Component and Federation Concept Models in a Federated Database System - Masood, Nayyer; Eaglestone, Barry (Malaysian Journal of Computer Science, 2003)
A methodology for assigning interpretation to a database schema and to develop a federation context in the form of concept models is presented. The concept models are developed using the concepts from an ontology that acts as a semantic fulcrum in the schema integration methodologies. The ontology provides a common vocabulary to establish concept models. The benefit of establishing the concept models is twofold. One, it provides an interpretation to the component schemas of a federated database system. In this perspective it compensates the lack of semantic expressiveness of the current data models. Second, it becomes easier to compare different component schemas and to identify semantic similarities among them that is an essential step in schema integration, hence providing a basis for a semi-automated schema integration approach.